Counselling Psychology in Australia: History, status and challenges. Issue 2 (2nd April 2016) - Di Mattia, Michael A.; Grant, Jan
Abstract : Counselling psychology in Australia has developed and matured since its emergence in the 1970s. This article provides a brief historical overview and situates counselling psychology (CP) in relation to other applied areas of psychology in Australia. A review of registration, professional organisations, work and role settings and core features is provided. Australian counselling psychologists work predominantly in private practice, as well as hospitals, counselling agencies, universities, medical practices, prisons and government departments. They provide assessment, diagnosis and treatment for mental health disorders and psychological problems related to adverse life events. In addition, they provide couple, family and group therapies. Challenges facing CP in Australia are explored, including a reduction in training programmes, inequities in funding for psychological services and tensions with the definition and description of the scopes of practice.